Answer:
(-3, -6, 0)
Step-by-step explanation:
3(-1) = -3
3(-2) = -6
3(0) = 0
Answer:
q=−3x3+4x2−x
hope this helped :)
Step-by-step explanation:
First expression
=> 3 x 3 x 3 x 3 x 3 – In this expression, we multiplied 3 5 times and the product is 243
Second expression
=> 3 ^ 5 , in where ^ read as raised to the power. , the product is also 243
Third expression
=> 3^2 x 3 ^3
=> (3 x 3) x (3 x 3 x 3)
=> 9 x 27, the product is also equals to 243.
30 + 5h = 20h
30 = 20h - 5h
30 = 15h
30/15 = h
2 = h
at 2 hrs, they both charge the same rate...
30 + 5(2) = 30 + 10 = 40
20h = 20(2) = 40
so at 2 hrs, they both charge $ 40
we are given
![y=-7x-4](https://tex.z-dn.net/?f=%20y%3D-7x-4%20)
![-y=7x+4](https://tex.z-dn.net/?f=%20-y%3D7x%2B4%20)
we can multiply -1 on both sides of second equation
![-1*-y=-1(7x+4)](https://tex.z-dn.net/?f=%20-1%2A-y%3D-1%287x%2B4%29%20)
![y=-7x-4](https://tex.z-dn.net/?f=%20y%3D-7x-4%20)
we can see that
both equations becomes same
so, they are coincident............Answer